Anti-inflammatory and wound healing effects of gel containing Kaempferia marginata extract. (10th August 2019) - Muthachan, Thawiwan; Tewtrakul, Supinya
Abstract: Ethnopharmacological relevance: Kaempferia marginata Carey (Zingiberaceae family) has been traditionally used in the treatment of inflammation. The whole plant decoction is used for treatment of fever. Ethanol extracts which exert potent anti-inflammatory properties are selected for wound healing assay. Aim of the study: This study aimed to investigate activities of the extract and gel formulation on anti-inflammatory and wound healing activities. The anti-inflammatory and wound healing properties from this plant could support its traditional uses and obtain a new pharmaceutical product with good physical, chemical and biological stabilities. Materials and methods: The anti-inflammatory activity was tested on anti-nitric oxide (NO) production using RAW264.7 cells and wound healing assay using human dermal fibroblast (HDF) cells. Results: The results found that the anti-inflammatory activity of gel containing K. marginata at 10% w/w showed the highest activity with an IC50 value of 12.50 μg/ml (Diclofenac gel, IC50 value = 64.90 μg/ml). It also revealed that wound healing activities of K. marginata gel (5% w/w) showed the highest % cell viability (134.05%) and the highest % cell migration at 85.20 using HDF cells. Conclusion: The present study shows that gel containing K. marginata extracts have good anti-inflammatory and wound healing properties in vitro . Graphical abstract: Image 1